Seasonal dynamics and primary production of the flora in a winter rye field in Finland - Halinen, Päivi; Raatikainen, Mikko (Agricultural and Food Science, 1991)
The total weed seed storage in the plough layer of 20 cm was 93 965 seeds/m2, of which 36 taxa were defined. The proportion of seeds of annual and winter annual species in soil was 89.6 %. The number of rye seeds emerging in autumn was 614 per m2 and weeds 224 per m2. The total number of weeds was 381/ m2 when the calculation was based on the time of maximal appearance. 0.3 % of the total amount of weeds emerged. Rye and Elymus repens were the dominant species in the above-ground vegetation, whereas the biomass of the other weeds remained poorly developed because of marked shading from these two. The maximum biomass of the living above-ground vegetation, 614 g/m2, was achieved in the middle of August (12. VIII). Net above-ground primary production, measured by the harvesting method, was 664 g/m2 · year and underground production 190 g/m2 · year, giving a total production of vegetation and detritus of 854 g/ m2 · year. The net efficiency of the primary producers was 0.7 %.